2002
DOI: 10.1302/0301-620x.84b1.12034
|View full text |Cite
|
Sign up to set email alerts
|

The external fixator compared with the sliding hip screw for pertrochanteric fractures of the femur

Abstract: In a prospective, randomised study we have compared the pertrochanteric external fixator (PF) with the sliding hip screw (SHS) in 100 consecutive patients who were allocated randomly to the two methods of treatment. Details of the patients and the patterns of fracture were similar in both groups. Follow-up was for six months. Use of the PF was associated with significantly less blood loss, a shorter operating time, reduced postoperative pain, shorter hospitalisation (p < 0.001), earlier mobilisation (p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 17 publications
6
46
1
5
Order By: Relevance
“…Postoperative pain is minimal and easily controllable, making the nursing and mobilisation of these patients easier. Studies using new fixators (Orthofix Pertrochanteric Fixator) have also shown that external fixation can provide results that are similar to, or even better than, those obtained with conventional internal fixation techniques [13,14]. Despite these evident advantages, the external fixator has failed to become popular with most surgeons because of the significant reported complications in previous studies, infection being the most common.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postoperative pain is minimal and easily controllable, making the nursing and mobilisation of these patients easier. Studies using new fixators (Orthofix Pertrochanteric Fixator) have also shown that external fixation can provide results that are similar to, or even better than, those obtained with conventional internal fixation techniques [13,14]. Despite these evident advantages, the external fixator has failed to become popular with most surgeons because of the significant reported complications in previous studies, infection being the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of deep infection that required pin removal or repositioning have been reported [5]. Vossinakis and Badras [14] reported that pintrack infection developed in 15 of their 50 patients (30%) treated with the Orthofix external fixator using standard pins. In a similar study, 18 of 41 patients (45%) had pintrack complications [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However a high prevalence of postoperative complications such as pin-loosening, infection, and mechanical failure of the fixator resulted in discontinuation of its use. 3,12 In the last decade, the advancement of external fixators and the introduction of new materials such as hydroxyapatite coated pins as well as better understanding of the mechanics of fracture healing in osteoporotic bone has prompted surgeons to reconsider external fixation as an alternative method for trochanteric fracture management. 13e16 The purpose of this study is to describe our outcomes of external fixation in management of trochanteric fractures in high-risk elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Yaşlılarda oluşan kalça kı-rıklarının tedavisinde amaç, hastanın mümkün olan en kısa sürede hareket etmesini sağlayarak kırık öncesi yaşamına geri döndürmek ve hareketsizliğe bağlı ölümle sonuçlana-bilecek komplikasyonların gelişmesini önlemektir. [1][2][3] İnstabil IFK'nda yeterli redüksiyon ve rijid internal fiksasyon günümüzde halen en geçerli tedavi yöntemidir. Biyomekanik ve anatomik uyumluluğu nedeni ile son yıllarda proksimal femoral nail (çivi) (PFN) ortopedik cerrahlar tarafından gün geçtikçe kullanımı artan bir fiksasyon materyali olarak dikkat çekmektedir.…”
Section: Introductionunclassified